Furan-Containing Chiral Spiro-Fused Polycyclic Aromatic Compounds: Synthesis and Photophysical Properties - Koji Nakano; Ko Takase; Keiichi Noguchi (Molecules, 2022)
Spiro-fused polycyclic aromatic compounds (PACs) have received growing interest as rigid chiral scaffolds. However, furan-containing spiro-fused PACs have been quite limited. Here, we design spiro[indeno[1,2-b][1]benzofuran-10,10′-indeno[1,2-b][1]benzothiophene] as a new family of spiro-fused PACs that contains a furan unit. The compound was successfully synthesized in enantiopure form and also transformed to its S,S-dioxide derivative and the pyrrole-containing analog via aromatic metamorphosis. The absorption and emission properties of the obtained furan-containing chiral spiro-fused PACs are apparently different from those of their thiophene analogs that have been reported, owing to the increased electron-richness of furan compared to thiophene. All of the furan-containing chiral spiro-fused PACs were found to be circularly polarized luminescent materials.